The Effect of Insecurity on Tourism Activities in Jos, Plateau State, Nigeria - Shenpam, Daniel Godwin; Dangle, Bala Hassan (International Journal of Humanities, Education, and Social Sciences, 2025)
The tourism sector in Jos, Plateau State, which was once a key driver of economic growth and local development, has experienced a severe decline due to the persistent insecurity in the state. This study examines the effect of insecurity on tourism activities in Jos, Plateau state. The study used a descriptive, cross-sectional survey research design. A sample size of 400 respondents was selected from the total population of 1,260,200 using the Tare Yamane formula. Questionnaires were distributed to 400 randomly selected respondents across Jos North, Jos South, and Jos East LGA. Interviews were also conducted with six key informants to complement the data gathered from the questionnaires. Responses from the questionnaires were analysed using descriptive statistics of frequency counts and percentages while quantitative data were analysed while outlining the key point presented by the key informant. The study revealed that insecurity in Jos has significantly affected tourism activities. Major effects include a decline in foreign investment, widespread unemployment, reduced patronage of tourist centres, and diminished state revenue. Insecurity also deters foreign investors, disrupts livelihoods in the tourism sector, and tarnishes Jos's reputation as a tourist destination. The study recommended that drones and CCTV cameras are examples of advanced technologies that should be used to provide real-time surveillance to identify and discourage criminal activity within the State.